Design and fabricate of cat feeder - Nurul Asqi, Md Rashid (2012)
This thesis represent about the new design concept of the cat feeder. Others cat feeder comes with a lot of choices and design but not all are really good for cats. Nowadays, people are getting busier with their life and sometimes forget to take such a good care for their cat’s eating time and need require some helps to ease the burden. The objectives of this thesis are to design and fabricate a manual and an entertaining of cat feeder. There are three design concepts have been suggested and by doing the scoring process, concept C has been chosen. This design consists of five parts and the used of bearing was the most critical part to be designed due to its cover casing spinning. After the fabrication, the dimension of this casing as well as the material selection becomes another critical factor while fabricating this cat feeder. After fabrication, it’s found out that this cat feeder also has wasted a lot of material and wrong of selection material which is zinc. Recommended material selection will be Acrylonitrile butadiene styrene (ABS) type of plastic.